A review of standard pharmacological therapy for adult asthma – Steps 1 to 5. (May 2015) - Patel, Mitesh; Shaw, Dominick
The aim of pharmacological therapy for asthma is to improve symptoms and lung function and minimize the risk of asthma attacks. The intensity of treatment is based on the level of asthma control and the potential risk of future deterioration. In the British asthma guidelines, treatments are divided into steps 1 to 5, with each step signifying a need for an increase in therapy in response to symptoms or to prevent exacerbations. Treatments comprise of inhaled or systemic medications. Inhaled therapy includes short-acting and long-acting medication to improve symptoms and inhaled corticosteroids that reduce airway inflammation. Systemic treatments include medications that act on specific biological pathways, such as the leukotriene or immunoglobulin E pathways, or systemic corticosteroids. In choosing a particular therapy, treatment benefits are balanced by the potential risks of medication-related adverse effects. This review will provide a practical guide to the key pharmacological therapies for adult asthma at steps 1 to 5 based on British guidelines and consider future options for new treatments.